Ultrasonographic identification of the cricothyroid membrane in a patient with a difficult airway as a result of cervical hematoma caused by hemophilia: a case report - Jimbo, Ippei (BMC Anesthesiol, 2019)
BACKGROUND: Surgical cricothyroidotomy is a last resort in patients with an anticipated difficult airway, but without any guarantee of success. Identification of the cricothyroid membrane may be the key to successful cricothyrotomy. Ultrasonographic identification of the cricothyroid membrane has been reported to be more useful than the conventional palpation technique. However, ultrasonographic identification techniques are not yet fully characterized. CASE PRESENTATION: A 28-year-old man with hemophilia and poor adherence to medication. He was brought to the emergency department with a large cervical hematoma and respiratory difficulty. An otolaryngologist decided to insert a tracheal tube to maintain his airway. However, emergent laryngoscopy indicated an anticipated difficult airway. A backup plan that included awake intubation by the anesthesiologists and surgical cricothyroidotomy by an otolaryngologist was devised. The cricothyroid membrane could not be identified by palpation but was detected by ultrasonographic identification with a longitudinal approach. Awake fiberoptic intubation was successfully performed. CONCLUSIONS: In this case, the cricothyroid membrane could be identified using the longitudinal approach but not the transverse approach. It may be ideal to know which ultrasound technique can be applied for each patient.